Incidence of Hypotension after Discontinuation of Norepinephrine or Arginine Vasopressin in Patients with Septic Shock: a Systematic Review and Meta-Analysis - Song, Jae-Uk (J Korean Med Sci, 2019)
BACKGROUND: There has been no consensus regarding the discontinuation order of vasopressors in patients recovering from septic shock treated with concomitant norepinephrine (NE) and arginine vasopressin (AVP). The aim of this study was to compare the incidence of hypotension within 24 hours based on whether NE or AVP was discontinued first in order to determine the optimal sequence for discontinuation of vasopressors. METHODS: A systematic literature search was conducted in MEDLINE, Embase, and the Cochrane Central Register. The primary end-point was incidence of hypotension within 24 hours after discontinuation of the first vasopressor. RESULTS: We identified five studies comprising 930 patients, of whom 631 (67.8%) discontinued NE first and 299 (32.2%) discontinued AVP first. In pooled estimates, a random-effect model showed that discontinuation of NE first was associated with a significant reduction of the incidence of hypotension compared to discontinuing AVP first (31.8% vs. 54.8%; risk ratios, 0.35; 95% confidence interval, 0.16 to 0.76; P = 0.008; I(2) = 90.7%). Although a substantial degree of heterogeneity existed among the trials, we could not identify the significant source of bias. In addition, there were no significant differences in intensive care unit (ICU) mortality, in-hospital mortality, 28-day mortality, or ICU length of stay between the groups. CONCLUSION: Discontinuing NE prior to AVP was associated with a lower incidence of hypotension in patients recovering from septic shock. However, our results should be interpreted with caution, due to the considerable between-study heterogeneity.